IMAGES OF HIGH-RISE BUILDING DOMINANTS AS A BRANDING TOOL FOR AIRPORTS AND THEIR ADJACENT AREAS - Agieieva, Galyna (Theory and practice of design, 2023)
The development of the area of airports has its specifics related to the safety of aircraft flights and technological processes of ground handling of air transportation. At the same time, development not only affects the urban development situation at airports and the areas located around them but also forms a well-established image of the airport as a component of a tourist destination. A special place is occupied by images of high-rise dominant buildings, which are airfield control towers. The implementation of creative ideas for forming the latter contributes to the recognition of the image of the airport and can be aimed at creating cultural resources of the airport environment and its adjacent areas. Purpose. The specifics of high-rise dominants of airport development and the main trends in their use in marketing technologies should be identified as graphic images of signs for goods and services. Methodology. The research includes the study of cartographic, graphic, photographic, and design materials, as well as it is based on published information from the history of design, construction, and operation of research objects. The main research methods are comparative and critical analysis, a systematic approach to studying an object as a complex and identifying its properties and connections with the environment. Results. The specifics of development used in marketing technologies are studied. High-rise dominants, which are buildings of airfield control towers, are determined as objects of increased urban planning and compositional significance of development. Scientific novelty. Typological characteristics (5) of locally placed high-rise dominants are determined, which makes it possible to create unique images of buildings using appropriate architectural, structural, and urban planning solutions. The corresponding levels of (3) formation of the architecture of buildings of airfield control towers are determined, each of which is innovatively attractive. The practice of using images of buildings of airfield control towers as graphic designations of services of several airports is studied (3). The reasons for the loss of functions by a building are the most characteristic features of a stable image of the architectural environment of airports. Practical significance. Proposals for the buildings of new airfield towers (2) are provided, the figurative solutions of which would facilitate recognizing the architectural environment of Ukrainian airports as components of tourist destinations.